THE COGNITIVE PSYCHOLOGY OF ISLAMIC PERSPECTIVE - Evita Yuliatul Wahidah (Amal Insani Foundation, 2020)
Cognitive psychology is often referred as intellectual psychology or intelligence. Human cognitive psychology is a psychological process that involves the process of obtaining knowledge, composing and using knowledge and other activities such as thinking, remembering, understanding, considering, observing, analyzing, synthesizing, evaluating and solving problems through interaction with the environment. While Islam has a unique view of man from his cognitive domain, his sheets contain divine guidance on the creation of man and human nature either explicitly or implicitly (brief interpretation) and offering problem solving over all the probabilities of his life. Including, the discourse of cognitive psychology. Departing from the paradigm, cognitive psychology of Islamic perspective the discussion becomes an interesting thing. In addition to find out the method of Islamization of developing science, also to explore the aspects of cognitive psychology in Islam based on the Qur'an and Hadith. The cognitive psychology of the Islam's perspective is also to provide an alternative to the criticism of modern psychology that breaks away from divine values.